The Term Delay and its Jurisprudences in the Section of Punishments and Felonies (Journal of the College of Education for Women, 2020)
Different Arabic and Islamic societies are free of evil instincts. Therefore, certain provisions of legitimacy came to stress the importance of the intentions of sharia to achieve the interests of all people that involve several aspects, including the five fundamental things: religion, oneself, offspring, mind and money. Almighty Allah has specified certain punishments on those who violate these things by imposing punishments on the part of the criminal to preserve souls. He imposes the penalty of theft to preserve property, the Hadd punishment for adultery to preserve the symptoms, the punishment on the drunk to preserve the mind, and the Hadd punishment for the apostate to preserve the religion. By the adherence to these punishments life will be preserved and will go on. This means that the constitution in force and our current laws delay the implementation of punitive provisions, including death penalty, which is not issued except by presidential decree. Besides, the human rights organizations, which emphasize the rights and freedom, consider the penalty of cutting the hands and stoning as violations of the sanctity of human body. This gave the perpetrators a legislative basis to allow them to persist in committing the crimes of murder, theft and adultery, which began to spread. Furthermore, the application of a penalty depends mainly on the testimony of witnesses which is difficult to fulfill in our courts for people avoid testifying in such crimes due to their fear of the absence of the law...